2011
DOI: 10.1179/2042645311y.0000000001
|View full text |Cite
|
Sign up to set email alerts
|

Influence of earlywood/latewood and ring position upon water vapour sorption properties of Sitka spruce

Abstract: Variation in the water vapour sorption kinetics of the stemwood of Sitka spruce (Picea sitchensis (Bong.) Carr.) has been studied, with respect to possible variations between earlywood and latewood and between different annual ring positions from pith to bark. The sorption kinetics was analysed using the parallel exponential kinetics (PEK) model that has recently been introduced by this laboratory for studies with wood. Significant differences in kinetic parameters were found between ring positions, correspond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 31 publications
4
16
0
Order By: Relevance
“…The slow process (t 2 ) adsorption and desorption do not show the same trend, instead there is no clear difference between the earlywood and latewood samples for the slow process. The fast process being quicker for earlywood samples than latewood samples with no difference in the slow processes, which is comparable to findings for another species of timber [23]. A statistical study of earlywood and latewood Sitka spruce sorption kinetics shows that the earlywood fast process responded to the changing RH significantly faster than the latewood samples [23].…”
Section: Characteristic Timessupporting
confidence: 76%
“…The slow process (t 2 ) adsorption and desorption do not show the same trend, instead there is no clear difference between the earlywood and latewood samples for the slow process. The fast process being quicker for earlywood samples than latewood samples with no difference in the slow processes, which is comparable to findings for another species of timber [23]. A statistical study of earlywood and latewood Sitka spruce sorption kinetics shows that the earlywood fast process responded to the changing RH significantly faster than the latewood samples [23].…”
Section: Characteristic Timessupporting
confidence: 76%
“…The isotherms and sorption kinetic behaviour of the celluloses was measured using a Dynamic Vapour Sorption Intrinsic apparatus (DVS, Surface Measurement Systems Ltd, London, United Kingdom) as previously reported (Hill et al 2010d;Xie et al 2010c). The mass of the cellulose sample (approximately 5 mg), running time, actual relative humidity (RH) were real-time recorded in a thermostatically controlled cabinet at 25°C during the sorption experiment.…”
Section: Determination Of Dynamic Water Vapour Sorptionmentioning
confidence: 99%
“…The fast adsorption process has been assigned to the ingress of water onto the microfibril surfaces and into amorphous regions between the microfibrils and the slow adsorption is associated with the opening up of new sorption sites (Okubayashi et al 2005a, b;Hill et al 2010;Xie et al 2010). However, it has recently been argued that this interpretation is not correct (Hill et al 2010d). It has been previously shown with thin wood samples that the diffusion kinetics is non-Fickian and that it is necessary to invoke substrate deformation as being the rate-limiting process during sorption (Christensen 1965;Krabbenhoft and Damkilde 2004).…”
Section: Introductionmentioning
confidence: 96%
“…Majka and Olek [12] determined higher EMC in the juvenile wood of Tilia sp. Hill et al [13] concluded that there was no relation between the sorption isotherms and the location of the sample in the tree in the wood of Picea sitchensis. Esteban et al [14] obtained higher EMC in mature wood of Abies pinsapo than in its juvenile wood.…”
Section: Introductionmentioning
confidence: 98%